Investigation of microstructure evolution and mechanical properties of gas tungsten arc welded dissimilar titanium (CP-Ti/Ti–6Al–4V) alloys - Kumar A.; Mahto M.K.; Rana V.S.; Vashista M.; Yusufzai M.Z.K. (My University, 2025)
Economical welding of dissimilar titanium alloys has always been a challenge for the aerospace and nuclear industries, where these alloys are extensively used because of their high strength-to-weight ratio. The present investigation deals with the development of a novel shielding setup for the successful welding of commercially pure titanium (α-phase) to Ti–6Al–4V ((α + β)-phase) without any atmospheric contamination using gas tungsten arc welding. Commercially pure titanium (CP-Ti) and Ti–6Al–4V sheets of 3 mm thickness were butt-welded autogenously and using CP-Ti filler metal. Metallographic studies, energy-dispersive X-ray spectroscopy, X-ray diffraction analysis, microhardness measurements, tensile testing, and fractography were carried out to understand the evolution of the microstructure and characterize the welds. Grain coarsening in heat-affected zone and weld, and variation in the distribution of phases were observed from the optical micrographs and energy-dispersive X-ray spectroscopy spectrum of different zones. An unsymmetrical variation of hardness was observed in the weld region, and a 15% reduction in hardness value (280 HV0.2) was obtained at the weld center of using filler metal weld than autogenous weld. Comparable strengths with little drop from as-received CP-Ti (307 MPa) were observed for welded specimens. Welds produced using CP-Ti filler metal (272 MPa) had higher strength than autogenous welds (214 MPa). As-received tensile specimens fractured nearly from the center of gauge length, but welded tensile specimens fractured near the base/heat-affected zone boundary of the CP-Ti side. © IMechE 2022.